ANALISIS KEPUASAN MASYARAKAT TERHADAP KUALITAS PELAYANAN KANTOR DESA SELACAU - nuzula, nuzula (JEBIM Prima, 2026)
In this study, the aim is to find out the extent to which the people in Selacau village feel satisfaction with the services that have been provided by the village office to the community. The type of research used in this study is quantitative. The population in this study is local residents of Selacau village, with a sample of 100 respondents. The test in this study uses the Linear Regression Test. Hypothesis testing used partial test (t) and simultaneous test (F), using SPSS 30.0.0.0 (20). The results of the partial test (t) show that the variable Quality of Service (X) has a significant effect on Community Satisfaction (Y). The results of the silmultan test (F) showed that there was a positive relationship between Service Quality and Community Satisfaction with a Fcount value of 42.175 > f table 3.94 with a significance obtained of 0.001 < 0.05, This indicates that the Service Quality variable has an effect on the Community Satisfaction variable